Perancangan Casual Edugame Mitigasi Bencana Gempa Bumi bagi Remaja Di Bandung - Dini Faisal; Irfansyah Irfansyah; Hilwadi Hindersah (Wimba : Jurnal Komunikasi Visual, 2013)
In general, Indonesian society is still don't understand the high level risk of earthquake hazard threat in their own region. Ignorance of this information can be very fatal for the society. City with developing infrastructure and high population density has higher risk of earthquake disasters. These two are the factors of vulnerability that make Bandung as a high risk city of earthquake disasters. The society needs to know about earthquake mitigation in order to minimize the risk of earthquake disasters. One way of informing and introducing earthquake mitigation is through mobile devices such as tablet. As we know, tablet provides entertainment such as casual games. Casual game about earthquake mitigation in tablet devices can be an educational tool packed in the form of entertainment. Society and teenagers in particular can obtain such information and knowledge in order to reduce the risk of accidents during the earthquake. Designing casual edugame of earthquake mitigation includes two phases, (a) identification and data analysis on earthquake mitigation and its stages and (b) designing the visual of the game. The identification and data analysis obtained through books, journals, theses, and previous news (print and electronic). Reviewing and studying similar games contribute in game's design process. The game has two stages where players will gain information about earthquake mitigation. Three main informations are: (a) conducting earthquake-proof facility, (b) preparing survival kit and (c) practicing "drop, cover and hold" responses. The game's story, characters and setting is the representation of everyday life in earthquake potential city. This game aims for teens awareness of their vulnerability and to prepare them for earthquake disaster risk. That way, this game will be able to introduce positive attitude towards their vulnerable environments.